Constructing international relations in the Arab world - Lawson, Fred Haley, 1952- (Stanford University Press, 2006)
Following the collapse of the Ottoman Empire, Arab nationalist movements first considered establishing a unified regional arrangement to take the empire's place and present a common front to outside powers. This book explores the emergence of an anarchic states-system in the twentieth-century Arab world.